PENGEMBANGAN MEDIA AUGMENTED REALITY (AR) PADA PEMBELAJARAN IPAS MATERI SISTEM PENCERNAAN MANUSIA KELAS V SEKOLAH DASAR - Ramiyati; Sri Sumartiningsih; Putri Yanuarita Sutikno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has encouraged innovation in education, one of which is the use of Augmented Reality (AR) as a learning medium. This study aims to examine the utilization of AR media in science and social studies (IPAS) learning, particularly on the topic of the human digestive system for fifth-grade elementary school students. The method used in this study is a literature review by analyzing various recent studies related to the development and implementation of AR in education. The results of the study indicate that AR-based learning media can enhance students’ learning motivation, conceptual understanding, and critical thinking skills. AR has also proven effective in visualizing abstract concepts into more concrete and interactive forms. Therefore, AR is highly recommended as an innovative learning medium for IPAS in elementary schools. However, the implementation of AR still faces several challenges, such as limited technological devices, lack of teachers’ competence in utilizing technology, and the need for adequate internet access. Thus, support from various stakeholders, including schools and the government, is necessary in providing facilities and training for teachers. In conclusion, Augmented Reality has great potential to be further developed and widely implemented in IPAS learning at the elementary school level to improve the quality of education in the digital era.